Data processing technology of remote sensing in glaciology - Підлісецька, Ірина Олександрівна; Сільвейстров, Г.; Томченко, О. (Київський національний університет імені Тараса Шевченка, 2016)
This article shows the analysis of remote sensing methods for needs of glaciology and trends of modern research. Remote sensing not only accelerates the process of investigation of natural resources, but also provides fundamentally new information about the nature of the Earth, its components, phenomena and processes, which cannot be obtained by conventional methods. For most of glacial regions of the world scientists continue collecting information about the current condition of glaciers and changes that occur to them. However, often it is difficult to organize direct observation of some glaciers because of their apartness. Therefore, the main method of such research is using remote sensing data. Here is an instance of remote sensing data processing technology on an example of the glacier Columbia (Alaska, USA) ice cover using modern GIS-package ArcGIS. For our research we used four Landsat satellite images during different years (1975, 1986, 2001, 2015) obtained through Earth Explorer Service of United States Geological Survey (USGS). Images have been synthesizing in various combinations of channels to improve displaying the object and its visual perception. We were able to estimate changes of the ice cover of the area for 40 years. We used a method of automated classification for determining glacier borders, which is based on snow index NDSI using. The result of work is a map of Columbia glacier ice cover changes for forty years, which has allowed exploring the dynamics of glacier retreat and demonstrates its border changes. Today remote sensing completely allows solving crucial problems of understanding the evolution of natural processes, such as glaciology research. Long-term monitoring of glaciers is currently one of the few ways to track global climate changing on the planet.

Проведено аналіз методів дистанційного зондування Землі (ДЗЗ) для потреб гляціології та тенденцій сучасних досліджень цього напряму. Дистанційні методи не тільки прискорюють процес дослідження природних ресурсів, але й дають принципово нову інформацію про природу Землі, її окремі компоненти, явища та процеси, які звичайними методами отримати неможливо. Представлено технологію оброблення даних дистанційного зондування на прикладі льодового покриву льодовика Колумбія (Аляска, США) за допомогою ГІС-пакету ArcGIS та з використнням космічних знімків серії супутників Landsat за різні роки, отримані через сервіс Earth Explorer Геологічної служби США (USGS). Розроблено картосхему змін льодового покриву льодовика Аляска продовж сорока років, яка дозволила прослідкувати динаміку відступання льодовика та наочно демонструє зміни його меж.
Технологія оброблення даних дистанційного зондування для потреб гляціології
Bilous V.V., Bodnar S.P., Kurach T.M., Molochko A.M., Patychenko H.O., Pidlisetska I.O. Dystantsiyne zonduvannya z osnovamy fotohrammetriyi [Remote sensing and basic theory of photogrammetry], Kyiv., 2011. [in Ukrainian] Kostyuchenko Y. Vykorystannya kosmichnoyi informatsiyi u vyvchenni hidrosfery: Zastosuvannya suputnykovykh sposterezhen’ dlya doslidzhen’ snihovoho i l’odovoho pokryvu [The use of space data in hydrosphere studying: The use of satellite observations for studying snow and ice cover]. Available at: http://geo-aerospace.blogspot.com/2014/10/blog-post_14.html. [in Ukrainian] Marusazh Kh. Analiz suchasnykh metodiv doslidzhennya kil’kisnykh parametriv l’odovykiv [Analysis of modern research methods of glaciers quantitative parameters] Lviv, 2014. [in Ukrainian] Sovremennye problemy hlyatsyolohii [Modern problems of glaciology] Available at: https://sites.google.com/site/glacioprob/. [in Russian] Tokareva O.S. Obrabotka i interpretatsyya dannykh dystantsyonnoho zondirovaniia Zemli: [Processing and interpretation of remote sensing data], Tomsk, 2010. [in Russian] Tolstokhat’ko V. A. Fotohrammetriia ta dystantsiine zonduvannia [Photogrammetry and Remote Sensing] Kharkiv, 2013. [in Ukrainian] Dyurgerov M. B. Reanalysis of Glacier Changes: From the IGY to the IPY, 1960–2008. 2010. [in English] Riggs, G., D. Hall, and V. Salomonson. “A Snow Index for the Landsat Thematic Mapper and Moderate Resolution Imaging Spectrometer.” Geoscience and Remote Sensing Symposium, IGARSS ’94, Volume 4: Surface and Atmospheric Remote Sensing: Technologies, Data Analysis, and Interpretation, 1994. [in English]
Keywords: дистанційне зондування Землі; гляціологія; льодовий покрив; дешифрування знімків; remote sensing; glaciology; ice cover; interpretation of satellite images